THE PROCESS OF WORD FORMATION TETUN LANGUAGE IN UMATOOS VILLAGE, KECAMATAN MALAKA BARAT, MALAKA DISTRICT, NUSA TENGGARA TIMUR - Ernesto Gustavo Tahu (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
Indonesia is an archipelago which consists of various ethnic groups. Each ethnic group has a regional language as its group identity. Regional languages ​​have a very important role in social and cultural life. The people of Umato'os Village who generally use the local language of Tetun as a means of interaction, the formation process that occurs in Tetun in Umato'os Village is a change if the root word undergoes a process of forming a Tetun word. This type of research is descriptive qualitative. Data collection techniques were carried out by observation and interviews. Data analysis using the equivalent method. To test the validity of the data, researchers used source triangulation. The result of this research is that Tetum is one of the regional languages ​​in the archipelago which is in the administrative area of ​​Malacca district, East Nusa Tenggara province. Tetun language has its own uniqueness in the affixation process, the affixation process in Tetun not only undergoes a change but also the affixation process has shown a person's activity. Language can be used as a means of communication that is alive and fostered by the Tetum-speaking community as well as a means of developing regional culture. Tetun also serves as the Mother Language (first language) for the Tetun speaking community.